Enhancing supply chain integrity in smes through dockerized blockchain architecture - Zherzherunov, P.; Shmatko, O. V.; Шматко, О. В. (ГО «Міжнародний центр наукових досліджень»; ТОВ«УКРЛОГОС Груп, 2025)
In today’s digital economy, ensuring the security, transparency, and traceability of data has become vital, particularly within supply chain management (SCM). Blockchain technology, with its decentralized and immutable structure, has demonstrated potential in addressing inefficiencies and trust-related issues in SCM. Despite its advantages, small and medium-sized enterprises (SMEs) have faced significant barriers to blockchain adoption, including high deployment costs, operational complexity, and a lack of technical expertise [1]. This thesis proposes a dockerized blockchain architecture designed to mitigate these challenges and make blockchain more accessible to SMEs.